STABILITY PROBLEM FOR SINGULAR STURM-LIOUVILLE EQUATION - Panakhov, E. S.; Ercan, A. (Inst Applied Mathematics, 2017)
We consider the stability of the inverse spectral problems associated with the Sturm-Liouville equation having singularity type l (l +1)/x(2). To obtain stability results, we use the method which was given firstly by Ryabushko for regular Sturm-Liouville operator. These results give a bound for the difference between the spectral functions and an estimation for the norm of the difference between the solutions of associated problems under some conditions.
Keywords: singular equation; stability; spectral function